Like father, like son? A comparison of absolute and relative intergenerational labour income mobility in Germany and the US - Maximilian Stockhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Are children better off than their parents? This highly debated question in politics and economics is investigated by analysing the trends in absolute and relative intergenerational labour income mobility for Germany and the US. High quality panel data is used for this purpose; the SOEP for Germany and the PSID for the US. In Germany, 67 per cent of sons born between 1955 and 1975 earned a significantly higher wage or salary than their fathers: Those with fathers from the lowest earnings bracket were particularly mobile in absolute terms. In contrast, the fraction of US sons earning more than their fathers is 60 per cent on average for the same cohorts. Their share decreased from 66 per cent in the 1956-60 birth cohort to 48 per cent in the 1971-75 birth cohort, while it almost did not change in Germany. Overall, absolute but also relative labour income mobility are larger in Germany than in the US. This indicates that economic growth has been distributed more broadly in Germany than in the US. While the majority of German males has been able to share in the country's rising prosperity and are better off than their fathers, US males continue to lose ground. Hence, Chetty et al. (2017) seem to be right when they say that the American Dream is slowly fading away.
Keywords: D63; J62; 330; absolute intergenerational mobility; inequality; Labour income distribution; relative intergenerational mobility